HIV risk management among sexual minority men in China: context, lived experience, and implications for pre-exposure prophylaxis implementation. Issue 6 (1st June 2022) - Wu, Yumeng; Meyers, Kathrine; Xie, Lu
Abstract: This study examined the social context and lived experience of HIV risk management among sexual minority men in China. An interpretative phenomenological analysis of 25 in-depth interviews with participants in five Chinese cities was undertaken. Findings show how men managed HIV risk in the context of high risk perception and anxiety, and strong perceived social discrimination and marginalisation. Men's choice of risk management strategies was influenced by their often-negative perceptions of gay community, social norms around condom use, and prior lived experience. Results underscore the importance of considering these contexts when planning pre-exposure prophylaxis (PrEP) implementation in China and highlight the need for strategies to address potential PrEP-related stigma among sexual minority men.